A potential tumor suppressor role of PLK2 in glioblastoma - Xiangping Xia; Peirui Wang; Hua Xiao; Qishan Ran; Yan Li; Shengtao Yao (FEBS Open Bio)
Glioblastoma (GBM) is a highly malignant brain tumor with limited treatment options. Polo‐like kinase 2 (PLK2), a member of the polo‐like kinase family, has been variably implicated in cancer, but its role in GBM has not been fully elucidated. We utilized RNA‐seq data from multiple databases, including Gene Expression Omnibus (GEO), the Cancer Genome Atlas (TCGA), and the Chinese Glioma Genome Atlas (CGGA), and conducted experiments on human glioma cell lines to explore PLK2's expression and function. The effects of PLK2 overexpression on GBM cell viability, proliferation, migration, cell cycle, and apoptosis were assessed, and the tumorigenic potential of PLK2 was evaluated in a mouse model. PLK2 was consistently downregulated in GBM tissues compared to normal brain tissues across several datasets. Overexpression of PLK2 in GBM cell lines U87MG and U251 reduced their tumorigenic potential and enhanced cell cycle arrest and apoptosis, with significant reductions observed in apoptosis markers. Our findings suggest that PLK2 may potentially function as a tumor suppressor in GBM. Hence, PLK2 overexpression could potentially be leveraged as a therapeutic strategy to inhibit tumor progression and enhance apoptosis, providing new avenues for GBM treatment.